2019
DOI: 10.3389/fphar.2019.00691
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Eph/Ephrin System as Anti-Inflammatory Strategy in IBD

Abstract: Besides their long-known critical role in embryonic growth and in cancer development and progression, erythropoietin-producing hepatocellular carcinoma type B (EphB) receptor tyrosine kinases and their ephrin-B ligands are involved in the modulation of immune responses and in remodeling and maintaining the integrity of the intestinal epithelial layer. These processes are critically involved in the pathogenesis of inflammatory-based disorders of the gut, like inflammatory bowel diseases (IBDs). Accordingly, our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 37 publications
(45 reference statements)
0
33
1
Order By: Relevance
“…Finally, our highly detailed, single-cell expression patterns provide multiple candidate pathways for targeted, bench-to-bedside treatments aimed at reestablishing normal functions of the main dysregulated cell types that we identified in sarcoidosis. Ephrin receptor signaling, upregulated in sarcoidosis CD14 monocytes, has been an attractive therapeutic target for both infection and cancer ( 52 ) and has recently been investigated as a therapy for Inflammatory Bowel Disease ( 53 ). A recent study found chloroquine, a drug commonly used in the treatment of autoimmune disease, could reduce HIF-1 α levels in sarcoidosis alveolar macrophages and reduce IL-17 and IL-1β production in sarcoidosis PBMC in response to anti-CD3 ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our highly detailed, single-cell expression patterns provide multiple candidate pathways for targeted, bench-to-bedside treatments aimed at reestablishing normal functions of the main dysregulated cell types that we identified in sarcoidosis. Ephrin receptor signaling, upregulated in sarcoidosis CD14 monocytes, has been an attractive therapeutic target for both infection and cancer ( 52 ) and has recently been investigated as a therapy for Inflammatory Bowel Disease ( 53 ). A recent study found chloroquine, a drug commonly used in the treatment of autoimmune disease, could reduce HIF-1 α levels in sarcoidosis alveolar macrophages and reduce IL-17 and IL-1β production in sarcoidosis PBMC in response to anti-CD3 ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…As regards colonic Eph/ephrin gene expression, TNBS application did not change the levels of mRNA transcripts of EphA2 and ephrin-A1, since single bands of similar intensity were detected in colonic tissues of S and CNT mice; neither the treatment with UniPR1331 at 25 mg/kg nor that with the recombinant protein EphA2 affected EphA2 or In the case of EphB4 mRNA also, whose levels, along with those of ephrin-B2, had been already presented for S, CNT and EphB4-treated mice by Grandi, Zini et al [7], neither the instillation of the haptenating agent nor that of UniPR1331 modified their production with respect to S tissues (Figure 6A,C). Concerning ephrin-B2 gene expression, the instillation of TNBS promoted the appearance of an additional mRNA band, corresponding to a splice variant of ephrin-B2 gene, with similar intensity in vehicle-treated and in UniPR1331-treated mice (Figure 6B,D).…”
Section: Treatment With Unipr1331 Did Not Influence Colonic Eph/ephrin Gene Expressionmentioning
confidence: 83%
“…Recently, our group has also focused attention on the involvement of the Eph/ephrin system in the control of acute and subacute inflammatory processes in the gut; we demonstrated that EphA/ephrin-A proteins take part in the local and remote injuries induced by mesenteric Pharmaceuticals 2021, 14, 502. https://doi.org/10.3390/ph14060502 https://www.mdpi.com/journal/pharmaceuticals Pharmaceuticals 2021, 14, 502 2 of 16 ischemia/reperfusion, an acute inflammatory condition, which is characterized by microvascular dysfunctions and by the loss of mucosal barrier integrity [6]. Conversely, type B Eph/ephrin proteins seemingly participate in the modulation of the immune responses activated in trinitrobenzene sulfonic acid (TNBS)-induced colitis [7], a conventional model of inflammatory bowel disease (IBD) with a major Th1 component.…”
Section: Introductionmentioning
confidence: 99%
“… 44 Increased expression of EFNB2 has been also found to enhance intestinal wound healing in patients with Crohn disease and may play a potential role in the EphB/ephrin-B system as a pharmacological target in intestinal inflammatory disorders. 56 , 57 …”
Section: Discussionmentioning
confidence: 99%